Sex differences in phenotypic modulation of microglia by early-life physical stress in a rat model of chronic primary low back pain - Singhal, Deepika; Husk, Jonathan R.; Greffrath, Wolfgang; Treede, Rolf-Detlef (Pflügers Archiv, 2025)
Chronic primary low back pain (cpLBP) is a leading contributor to years lived with disability. Early-life stress is a major risk factor predisposing to cpLBP later in life upon minor injuries. We investigated sex differences in the involvement of microglia in the pathophysiology of early-life stress effects on pain responses to a secondary stimulus in adulthood. During adolescence, male and female Wistar Han rats underwent repeated restraint stress for 12 consecutive days, while controls were handled. In adulthood, acute LBP was induced by NGF or saline injections into the lumbar multifidus muscle. Subsequently, the animals were sacrificed and perfused for spinal cord extraction. A total of 3516 microglia cells were classified into three functional states (surveillant, primed, activated) using partition around medoids clustering and UMAP dimensionality reduction methods for eight 3-dimensional morphological features obtained from MATLAB 3DMorph. Across all conditions, the proportion of surveillant microglia was significantly higher in females than in males (p < 0.0001, d = 1.85), while males had more primed (p < 0.0001, d = 1.56) and activated (p < 0.01, d = 1.87) microglia. Priming by stress led to an increase in activated microglia after NGF injection (p < 0.05, d = 0.63), more distinct in males (p < 0.05, d = 0.82) than in females (p > 0.05, d = 0.43). Additive effect of stress and NGF caused a shift towards primed state in males (p > 0.05, d = 0.62), but not in females. In conclusion, stress was confirmed to play a critical role in priming microglia and predisposing to cpLBP. Sex differences previously shown for neuropathic pain were found to be also relevant in this more frequent musculoskeletal pain condition.